Interpersonal Communication in Improving Leadership Skills - Eric Krisna Sandi; RR Roosita Cindrakasih (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of interpersonal communication in improving leadership skills and identify factors that influence its effectiveness. Good communication helps leaders build trust, increase motivation, and strengthen relationships with the team. The research method used is the Systematic Literature Review (SLR), by collecting and analyzing studies from academic databases such as Google Scholar, Scopus, and ScienceDirect. The literature analyzed includes aspects of communication in leadership, such as listening skills, providing feedback, and utilizing technology. The results of the study indicate that effective interpersonal communication contributes to improving leadership skills, building team loyalty, and creating a productive work environment. The identified barriers include lack of leader communication skills, differences in communication styles, and work environment disruptions. Therefore, strategies such as communication training, an open organizational culture, and adaptation of digital communication are needed. In conclusion, good interpersonal communication is the main foundation of effective and influential leadership. By mastering the right communication skills, leaders can improve the effectiveness of decision making and encourage the achievement of organizational goals more efficiently.